Giant cell tumor of the extensor hallucis longus tendon sheath: a rare case report - Ankit Ashok Nyamagond; K. Nikil Gowda; A. S. Jasmal; Prabhat Mittal (MGM Journal of Medical Sciences)
Background: Giant cell tumors (GCTs) are benign soft tissue tumors characterized by slow growth. They are more commonly observed in females than males, with a female-to-male ratio of 1.5:1. These tumors predominantly affect individuals aged 15–40, accounting for 70%–80% of cases. GCTs are typically found on the hand’s tendons, but their occurrence in the foot is uncommon. This report describes a rare case of a GCT involving the extensor hallucis longus (EHL) tendon. Case Presentation: A 26-year-old male presented with swelling on the dorsum of the right foot, extending from the ankle joint line to the base of the great toe. The mass measured approximately 15 × 3 cm along the EHL tendon. The overlying skin appeared normal, and the swelling was non-tender with a variable consistency. No sensory or motor deficits were noted. Magnetic resonance imaging revealed a tenosysnovial GCT affecting the EHL tendon. Surgical excision of the tumor was performed, successfully preserving the EHL tendon. Conclusion: The preferred treatment for GCTs is complete surgical excision with clear margins. In cases with a high risk of recurrence or incomplete excision, adjuvant radiotherapy may be considered.